Impact of a recreational program in the resilience of 7th grade students at elementary school - Romero Barquero, Cecilia Enith (2017)
The investigation had the objectives of measuring the impact of a recreational program in the promotion of resilience, as well as its dimensions according to sex, and determine if the hours of participation, the number of recreational activities and the number of sessions was related to the levels of resilience and its dimensions. The experimental group was composed of 19 subjects, with an average age of 12.9. All attended were in seventh grade in an elementary school in the Talca region, Chile. The design was quasi-experimental of a non-equivalent pre-test-posttest control group. We used a mixed variance analysis of three tracks with repeated measures in a factor, and partial correlation. The results allowed us to observe the absence of a significant interaction (p < .05) among the group measured by sex, with regard to resilience and its dimensions. On the other hand, there has been significant interaction (p < .05) between measurements per group in resilience and in four dimensions. The experimental group significantly increased the value of resilience after intervention. Finally, the network-models dimension was significantly and negatively related with the number of hours.